Socio-economic status of the participants. - Sohini Paul (17965575) (2025)
Background Despite national declines in HIV prevalence, adolescent girls and young women (AGYW) in India remain disproportionately vulnerable to sexually transmitted infections (STIs), including HIV. This vulnerability stems from a convergence of biological, social, and structural factors, including early marriage, gendered expectations, poverty, and limited access to sexual and reproductive health (SRH) information and services. While prior research has documented these determinants, few studies explore how they intersect and evolve to shape AGYW’s lived experiences of risk, particularly within the general population. Methods This qualitative study used an adapted socio-ecological framework (which conceptualizes how structural, community, and individual-level factors interact to influence health and vulnerability) to examine the pathways of vulnerability to STIs and HIV among AGYW aged 16–24 in two urban regions: Delhi NCR and Mumbai. Data were collected through 42 in-depth interviews (IDIs), 4 focus group discussions (FGDs), and 18 key informant interviews (KIIs) with health providers, NGO staff, and program implementers. Reflexive thematic analysis was applied, guided by deductive codes from the eco-social model and inductive insights from participants’ narratives. Results Findings show that AGYW’s vulnerability is shaped by interconnected macro (e.g., early marriage, patriarchal norms), meso (e.g., school-based silences, provider bias), and micro (e.g., relationship coercion, low self-efficacy) level factors. Although some AGYW had SRH knowledge, stigma, lack of autonomy, and unsupportive environments often constrained its use. Married and low-income AGYW were particularly disadvantaged, while non-governmental organizations (NGOs) played an important but uneven role—offering crucial safe spaces for awareness and support, yet limited by inconsistent coordination and resources. Conclusion AGYW’s vulnerability to STIs/HIV in urban India is produced through dynamic and intersecting structural, institutional, and interpersonal constraints. Addressing these requires integrated, gender-sensitive interventions that promote agency, reduce stigma, and foster collaboration between NGOs and public systems. Programs must go beyond awareness to reshape the environments in which AGYW make sexual health decisions.